A Study on Correlation between Ultrasonic Pulse Velocity Method and Coarse Aggregate for Estimating Residual Modulus of Elasticity of Concrete Exposed to High Temperatures - Wonchang Kim; Keesin Jeong; Taegyu Lee; Sungyu Park (Applied Sciences, 2022)
In this study, the mechanical properties of normal concrete (NC) and lightweight concrete (LC) were measured upon exposure to high temperatures (20, 100, 200, 300, 500, and 700 °C). Then, analysis was conducted to predict the residual modulus of elasticity through ultrasonic pulse velocity. Crushed granite aggregate was mixed as the coarse aggregate for NC and coal-ash aggregate for LC. The effect of the water-to-binder (W/B) ratio (0.41, 0.33, and 0.28) on the mechanical properties (residual compressive strength, residual ultrasonic pulse velocity, residual modulus of elasticity, and stress–strain) of concrete was determined. The residual compressive strength, residual ultrasonic pulse velocity, and residual modulus of elasticity were higher for LC compared to NC. The correlation between the ultrasonic pulse velocity and residual modulus of elasticity was also analyzed, which yielded a high correlation coefficient (R2) at all levels. Finally, equations for predicting the residual modulus of elasticity using ultrasonic pulse velocity with R2 values of 0.94 and 0.91 were proposed for NC and LC, respectively.